(untitled) (Journal of Hama University, 2021)
The use of additive manufacturing systems in dentistry has been a widespread phenomenon. Additive manufacturing technology is defined as the fabrication of a 3D model or prototype by agglomerating the biomaterials layer by layer in a specific pattern dictated by the computer-aided design software. With the aid of this technology; structures with superior are rapidly, precisely, and inexpensively fabricated for direct medical utilization. In contemporary dentistry, manifold additive manufacturing techniques have been developed for the fabrication of fixed prosthetic restorations, removable dentures, surgical guides, individualized implants, custom impression trays, and anatomical models. Of these; stereolithography(SLA), selective laser sintering(SLS), selective laser melting(SLM), fused deposition modeling(FDM), and electron beam melting(SEBM) are commonly used. However, scientific data regarding their material options and working principles are still insufficient. Therefore, the aim of this review is to study the common additive manufacturing techniques in prosthetic dentistry .